2020
DOI: 10.5603/pmpi.2020.0008
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate palliative care education and curricular issues in Central Asia, Eastern and South-Eastern Europe: Results from a quantitative study

Abstract: Introduction. The WHO Europe Office, together with the European Association for Palliative Care, is supporting the development of an interdisciplinary core curriculum for health care professionals in the European Region, which is to be given to the countries as a recommendation. Material and methods. Between April and September 2018, a research journey to Central Asia, Eastern and SouthEastern Europe took place. It covered two main tasks: collecting quantitative data using a survey and collecting qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Before entering the field, we surveyed all five medical schools in Israel. The survey has been tested and used in the Pan-European study regarding postgraduate PC education to gain internationally comparable as well as country-specific data (Stähli et al, 2020). The survey included questions on (1) background information of the respondent, (2) voluntary and obligatory courses on PC, (3) PC content in different course models, (4) teaching methods, (5) time frame, (6) content, (7) institutions involved, (8) and examinations.…”
Section: Methodsmentioning
confidence: 99%
“…Before entering the field, we surveyed all five medical schools in Israel. The survey has been tested and used in the Pan-European study regarding postgraduate PC education to gain internationally comparable as well as country-specific data (Stähli et al, 2020). The survey included questions on (1) background information of the respondent, (2) voluntary and obligatory courses on PC, (3) PC content in different course models, (4) teaching methods, (5) time frame, (6) content, (7) institutions involved, (8) and examinations.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that GPs report the need for ongoing palliative care training. 15,16 Often, these courses are designed by specialist services; however, unless the content has practical application to the GP, they will be less effective. 17 Co-designing our educational intervention allowed us to resolve any discordance between the priorities of the expert and the participants, as well as deliver the material in an engaging format.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The course was free of charge. Since this is a preliminary project serving as a pilot with the intent to be modified based on teachers' experiences and participants' feedback, no formal certification by professional associations for Continuous Medical Education (CME) was obtained [10,11,15].…”
Section: Settingmentioning
confidence: 99%
“…Palliative care leaders and educators from 23 countries unanimously agreed that the main barriers to the development of educational work are limited political interest, insufficient educational structures, missing curricula, lack of trainers, and structural constraints of the health care system. They equally agreed that a European recommendation for a multidisciplinary post-graduate training would be of great importance [15].…”
Section: Introductionmentioning
confidence: 99%